Non-muscle Myosin II: Role in Microbial Infection and Its Potential as a Therapeutic Target - Tan, Lei; Yuan, Xiaomin; Liu, Yisong; Cai, Xiong; Guo, Shiyin; Wang, Aibing (Frontiers in Microbiology, 2019)
Currently, the major measures of preventing and controlling microbial infection are vaccinations and drugs. However, the appearance of drug resistance microbial mounts is main obstacle in current anti-microbial therapy. One of the most ubiquitous actin-binding proteins, nonmuscle myosin II (NM II) plays a crucial role in a wide range of cellular physiological activities in mammals, including cell adhesion, migration, and division. Nowadays, growing evidence indicates that aberrant expression or activity of NM II can be detected in many diseases caused by microbes, including viruses and bacteria. Furthermore, an important role for NM II in the infection of some microbes is verified. Importantly, modulating the expression of NM II with small hairpin RNA (shRNA) or the activity of it by inhibitors can affect microbial-triggered phenotypes. Therefore, NM II holds the promise to be a potential target for inhibiting the infection of microbes and even treating microbial-triggered discords. In spite of these, a comprehensive view on the functions of NM II in microbial infection and the regulators which have an impact on the roles of NM II in this context, is still lacking. In this review, we summarize our current knowledge on the roles of NM II in microbial-triggered discords and provide broad insights into its regulators. In addition, the existing challenge of investigating the multiple roles of NM II in microbial infection and developing NM II inhibitors for treating these microbial-triggered discords, are also discussed.